The effect of poor materials management in the construction industry: A case study of Abuja, Nigeria - Idowu Albert (University of the Free State, 2021)
Effective materials management on construction sites is handled carelessly by construction practitioners. This may result in several challenges such as materials waste generation, poor quality of work, project delays, and poor materials flow. Construction practitioners in Abuja, Nigeria, do not understand the consequences of these challenges to construction projects. This article investigates the effect of poor materials management on materials waste, quality of work, and project profitability in construction projects in Nigeria. A qualitative research approach was adopted in the study which included collective case study investigations. The population for the study was ongoing building project sites (ten case studies purposefully selected) in Abuja. The research instrument was direct-covert observation by the researchers to observe and record the construction processes, people’s behaviour, actions and interactions relating to materials management. The construction processes observed included materials usage onsite, loading/offloading of materials from procurement, storages, as well as materials handling and movement on site. Recording sheets with checklists were pre-set with statements (Likert items) and responses to observe and document the effect of poor materials management. The statements were rated on an ordinal three-point Likert scale. The observed/collected data were analysed using descriptive methods to determine the modal values. The findings from the study revealed that poor materials management has a considerable effect on material waste generation on any construction project site; moderate effects on quality of building projects, and both considerable and moderate effects on profitability in the construction projects. Based on these findings, it can be concluded that effective management of materials in construction projects would reduce the amount of waste generation, increase the quality of construction work, and offer optimum profitability to construction contractors. It is, therefore, recommended that the construction industry in Nigeria should collaborate with government agencies to develop guidelines for preparing a waste management plan for the construction industry.